2019
DOI: 10.18502/ijph.v48i5.1796
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Consequences of Breast Cancer in Iran: A Meta-Analysis

Abstract: Background: Breast cancer is known as one of the most common cancers among women and has severe psychological effects. This study aimed to identify the psychological consequences of breast cancer in previous studies based on meta-analysis. Methods: Meta-analytic procedures were conducted by Prisma guidelines. A literature search was conducted by using following electronic databases including scientific information databases (SID), Magiran, Medlib, ScienceDirect, PubMed, Google Scholar, Web of Science, Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
(18 reference statements)
0
10
0
1
Order By: Relevance
“…In a meta‐analysis done in Iran, they identified seven different psychological consequences of breast cancer. Among them, low quality of life ranked 3rd, and undesirable emotional, adaptive strategies in coping strategies were the fifth (Refaee Saeedi et al., 2019). A systematic review revealed that emotion‐focused behaviours and seeking social support were the main coping strategies used by Iranian women with breast cancer, especially in the early diagnosis phase (Mehrabi et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a meta‐analysis done in Iran, they identified seven different psychological consequences of breast cancer. Among them, low quality of life ranked 3rd, and undesirable emotional, adaptive strategies in coping strategies were the fifth (Refaee Saeedi et al., 2019). A systematic review revealed that emotion‐focused behaviours and seeking social support were the main coping strategies used by Iranian women with breast cancer, especially in the early diagnosis phase (Mehrabi et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of studies, it was found that the main alterations in these patients were: anxiety, alterations in body image, depression, fatigue and sexual dysfunction. 12 The most important finding of our research was the high frequency of family crises, especially those of a moderate degree (48%). Almost two thirds of patients had a nuclear family, which provides an adequate structure to face the health-disease process, 13 however, there was dysfunction in more than half of the families, which has a significant impact; the combination of these family factors and the disease itself could explain the high frequency of crises found in these patients (89%).…”
Section: Discussionmentioning
confidence: 57%
“…Breast cancer was the most prevalent cancer among women and the second leading cause of cancer death in women ( 40 , 41 ). Evidence suggested that depression was one of the most common psychiatric disorders in breast cancer patients, with over half (58%) of patients within the female breast cancer population experiencing mild depressive symptoms and 38% experiencing major depression ( 42 , 43 ). Mindfulness-based cognitive therapy (MBCT) was currently an effective intervention for psychiatric disorders associated with cancer treatment.…”
Section: Discussionmentioning
confidence: 99%